2020
DOI: 10.1242/jcs.246025
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal helix of BubR1 is essential for CENP-E-dependent chromosome alignment

Abstract: During cell division, misaligned chromosomes are captured and aligned by motors before their segregation. The CENP-E motor is recruited to polar unattached kinetochores to facilitate chromosome alignment. The spindle checkpoint protein BubR1 (also known as BUB1B) has been reported as a CENP-E interacting partner, but the extent to which BubR1 contributes to CENP-E localization at kinetochores has remained controversial. Here we define the molecular determinants that specify the interaction between BubR1 and CE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…Firstly, CENP-E is a plus-end directed kinesin-7 motor bound to kinetochores, which has been identified as a component of the outer kinetochore [ 11 ] and has a role in the reinforcement of kn-mt binding, in the alignment to the spindle equator of mono-oriented chromosomes and in the spindle assembly checkpoint; however, how CENP-E is recruited in kinetochores is still debated. Recent works confirmed the previous observation that BubR1 is responsible for the initial recruitment of CENP-E in kinetochores [ 12 ], although other BubR1-indipendent mechanisms are involved in recruiting CENP-E in unattached kinetochores [ 13 ]. The role of CENP-E in ensuring stable kn-mt capture is finely regulated by aurora kinases A and B and PP1 with a phosphorylation–dephosphorylation switch mechanism [ 14 ].…”
Section: Introductionsupporting
confidence: 79%
“…Firstly, CENP-E is a plus-end directed kinesin-7 motor bound to kinetochores, which has been identified as a component of the outer kinetochore [ 11 ] and has a role in the reinforcement of kn-mt binding, in the alignment to the spindle equator of mono-oriented chromosomes and in the spindle assembly checkpoint; however, how CENP-E is recruited in kinetochores is still debated. Recent works confirmed the previous observation that BubR1 is responsible for the initial recruitment of CENP-E in kinetochores [ 12 ], although other BubR1-indipendent mechanisms are involved in recruiting CENP-E in unattached kinetochores [ 13 ]. The role of CENP-E in ensuring stable kn-mt capture is finely regulated by aurora kinases A and B and PP1 with a phosphorylation–dephosphorylation switch mechanism [ 14 ].…”
Section: Introductionsupporting
confidence: 79%
“…No effects on mitotic spindle assembly were observed [ 96 ]. CENPE possesses at the C-terminus a kinetochore-binding domain that allows the interaction with kinetochore proteins BUBR1, CENPF, Ndc80, and HsNUF2 [ 86 , 97 ]. Instead, an ATP-dependent microtubule-binding site is present at the N-terminus, which is used for hydrolyzing ATP to generate mechanical forces along microtubules and is essential for CENPE localization at mitotic spindles [ 98 ].…”
Section: Microtubule Targeting Agents (Mtas) In Brain Tumorsmentioning
confidence: 99%
“…Interestingly, T608 phosphorylation on BubR1 appears to be related to certain CENP-E functions. Recent results confirmed that CENP-E and BubR1 interact through a C-terminal helix within the BubR1 kinase domain which may be necessary for CENP-E recruitment to the kinetochore via BubR1 [ 61 ]. It has also been postulated that the interaction between BubR1 and CENP-E through the BubR1 kinase domain stimulates BubR1s supposed kinase activity, allowing it to phosphorylate, among other substrates, itself at T608 [ 59 ].…”
Section: Phosphorylation Of Bubr1mentioning
confidence: 89%
“…BubR1 and CENP-E are thought to colocalize at kinetochores prior to T608 phosphorylation [ 59 , 61 , 65 ]. The presence of kinetochore–microtubule attachment errors stimulates Aurora B activity to phosphorylate KMN proteins and CENP-E, causing destabilization of the kinetochore-microtubule attachments [ 66 , 67 ].…”
Section: Phosphorylation Of Bubr1mentioning
confidence: 99%